Design and implementation of augmented reality technology in m-commerce based creative patents - Zuhri Halim; Muhammad Fatkhur Rahman (Enrichment : Journal of Management, 2023)
This research became carried out on Jl. Narogong, Perum. Limus Pratama Regensi, Blok A No.27 – Cileungsi, West Java in June 2019 via interviewing Creative Patent owners due to the fact the advertising gadget for Creative Patent merchandise handiest uses social media and sales facts series is still guide. The purpose of this studies is to provide a sales software this is able to introduce and market merchandise efficaciously with augmented fact functions, assist in recapping orders to minimize communication mistakes and make it simpler to find product income statistics extra successfully. M-commerce programs built based on cellular programs for users and web sites for admins. The research methodology used is the intense programming method and is designed the use of the Unifield Modeling Language (UML). The results of testing records using a questionnaire tool show a median value of eighty four.Eight%. The conclusion of this observe M-commerce programs designed for mobile make it clean for Creative Patent clients to access records related to shopping for and promoting transactions whenever and anywhere they're.